1998
DOI: 10.1021/ic9801239
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Thermal and Chemical Behaviors of Tartrate and Succinate Intercalated Zn3Al and Zn2Cr Layered Double Hydroxides

Abstract: Tartrate and succinate anions have been intercalated in Zn(3)Al and Zn(2)Cr LDHs. The preparations using either coprecipitation, anion exchange, or reconstruction methods are described. In the case of tartrate-containing LDH, coprecipitation and reconstruction methods have proved to be very limited to lead to pure materials due to the particular reactivity of tartrate anions. Intercalation of both anions under room-temperature conditions gives rise to expanded LDH with similar basal spacing. Moderate thermal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 18 publications
9
76
0
5
Order By: Relevance
“…Many organic-anion-pillared LDHs exhibit similar structural features. [10] The turbostratic effect is caused by a decrease in the ordering along the stacking axis due to the loss of van der Waals interactions between adjacent layers and the absence of a densely packed interlayer space formed by high charge density anions such as carbonate. On comparing the powder XRD patterns shown in Figure 1, it is evident that Zn 2 AlϪFcCOO exhibits increased turbostratic disorder because the hkl reflections are broader and less intense, and in fact several are not observed.…”
Section: Structural and Compositional Analysismentioning
confidence: 99%
“…Many organic-anion-pillared LDHs exhibit similar structural features. [10] The turbostratic effect is caused by a decrease in the ordering along the stacking axis due to the loss of van der Waals interactions between adjacent layers and the absence of a densely packed interlayer space formed by high charge density anions such as carbonate. On comparing the powder XRD patterns shown in Figure 1, it is evident that Zn 2 AlϪFcCOO exhibits increased turbostratic disorder because the hkl reflections are broader and less intense, and in fact several are not observed.…”
Section: Structural and Compositional Analysismentioning
confidence: 99%
“…Whilst a grafting phenomenon at low temperature has been reported for LDHs with both oxygen-containing and non-oxygen-containing anions, [19][20][21][22][23][24] other authors have suggested that the thermally metastable phase originates from a reorientation of the anions in the interlayer domains rather than from such a grafting process. [25][26][27][28][29][30] In this work, we report the intercalation of transition metal complexes [ (where Y denotes edta 4-) into MgAl LDHs with different Mg/Al ratios, by a hydrothermal synthesis method. Our aim is to clarify the factors affecting the orientation of the complexes, particularly in the temperature interval 30-400°C, in order to understand the evolution of the interlayer phase with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…ZnCr-LDH was prepared by using the coprecipitation method, which was similar to that reported by Corinne Depge et al [41] Typically, 40 mL aqueous solution containing Zn(NO 3 ) 2 ·6 H 2 O (7.85 g) and Cr(NO 3 ) 3 ·9 H 2 O (4.57 g), and another aqueous solution containing NaOH (8.0 g/100 mL H 2 O) were simultaneously added to 150 mL DI water, and the pH of the slurry was maintained at approximately 5.5 AE 0.5 under continuous stirring. The resulting slurry was continuously stirring for 12 h at room temperature and then aged 24 h at 80 8C.…”
Section: Synthesis and Exfoliation Of Zncr-ldhmentioning
confidence: 75%